Influence of Transformational Leadership and Work Engagement On Innovative Behavior - Nafiah Ariyani; Sri Hidayati (Faculty of Economic and Business, 2018)
Innovative behavior, employee engagement and transformational leadership are critical variables that should be the focus of every organization’s this era of rapid technological change. This study aims to determine the effect of transformational leadership and work engagement on innovative behavior in the banking industry in Indonesia. The technique sampling is purposive sampling, so the numbers of samples are 378 people. The Data analysis technique is multiple linear regression analysis. The results show that transformational leadership and work engagement have a significant and positive effect on innovative behavior, in which work engagement as a mediating variable will to the positive influence of transformational leadership on innovative behavior. These findings suggest that it is necessary to apply transformational leadership styles and increase employee engagement to improve innovative employee behavior.DOI: 10.15408/etk.v17i2.7427